PENERAPAN DOKUMENTASI KEPERAWATAN MENGGUNAKAN 3S (SDKI, SLKI, SIKI) DI RSI BANJARNEGARA - Tri Sumarni; Adiratna Sekar Siwi; Arni Nur R; Anton Suhendro (LPPM Universitas Harapan Bangsa Purwokerto, 2022)
Nursing documentation is the primary source of clinical information for meeting legal and professional requirements. The problem that still often arises in the implementation of documentation is that it is not in accordance with the Standardized Nursing Language (SNL) standard of nursing language, especially uniformity in using the language of nursing diagnoses and interventions. The community service program aims to increase nurses' knowledge about how to formulate nursing diagnoses using the SDKI, how to formulate outcome criteria using the SLKI and how to formulate nursing activities based on the SIKI. The method of service implementation is screening nurses' knowledge about nursing documentation using 3S, counseling and discussions about nursing documentation using 3S and its application. The target of the activity is 35 nurses. Most of the service participants are 20-30 years old (54%), female (69%), have D3 Nursing education (91%) and have worked for more than 3 years (54%). Regarding knowledge about nursing documentation using 3S, before health education the level of knowledge was mostly in the poor category (68%) and after health education the level of knowledge was in the good category (60%). .